Recent progress in graphene-reinforced aluminum matrix composites - SU, Jinlong; TENG, Jie (Frontiers of materials science, 2021)
Recent years witnessed a growing research interest in graphene-reinforced aluminum matrix composites (GRAMCs). Compared with conventional reinforcements of aluminum matrix composites (AMCs), graphene possesses many attractive characteristics such as extremely high strength and modulus, unique self-lubricating property, high thermal conductivity (TC) and electrical conductivity (EC), and low coefficient of thermal expansion (CTE). A lot of studies have demonstrated that the incorporation of graphene into Al or Al alloy can effectively enhance mechanical and physical properties of the Al matrix. The purpose of this work is aimed to trace recent development of GRAMCs. Initially, this paper covers a brief overview of fabrication methods of GRAMCs. Then, mechanical, tribological, thermal and electrical properties of recently developed GRAMCs are presented and discussed. Finally, challenges and corresponding solutions related to GRAMCs are reviewed.